2008
DOI: 10.5020/18061230.2008.p112
|View full text |Cite
|
Sign up to set email alerts
|

Farmacoterapia adjuvante no tratamento da dor oncológica

Abstract: RESUMOObjetivo: Avaliar o tratamento farmacoterapêutico adjuvante analgésico em pacientes oncológicos. Métodos: Analisaram-se os prontuários de 63 pacientes portadores de neoplasias malignas, que também responderam a uma entrevista constando os seguintes dados: descrição da dor quanto à localização, intensidade (pela escala numérica de 0 a 10) e alívio. Além disso, os esquemas analgésicos foram agrupados em compatível e não compatível, baseando-se na escala analgésica (Numeral Rating Scale) da Organização Mund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
1
2
0
4
Order By: Relevance
“…Our study has compared analgesia offered to patients with verbal pain complaints to that recommended by the WHO. The same comparison was made in the study by Barbosa et al 15 . Both studies have observed prevalence of not compliance with WHO guidelines.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Our study has compared analgesia offered to patients with verbal pain complaints to that recommended by the WHO. The same comparison was made in the study by Barbosa et al 15 . Both studies have observed prevalence of not compliance with WHO guidelines.…”
Section: Discussionsupporting
confidence: 54%
“…In case of onco-hematologic patients, another limitation was restriction to the use of nonsteroid anti-inflammatory drugs for pain, because it could inhibit a possible fever and mask a signal indicating infection, especially in leucopenia patients. The use of adjuvant analgesics is still very limited, being antispasmodic the most frequently prescribed class 15 . WHO tries to publicize and encourage the use of other adjuvant classes as important for effective pain control, such as antidepressants (amitriptyline), anticonvulsants (phenytoin, phenobarbital) and hypnotics (midazolam).…”
Section: Discussionmentioning
confidence: 99%
“…The main drug interactions found in the drug-interaction analysis are shown in Table 5. 19 showed a mean number of 6 drugs taken by AD patients, while other authors, such as Barbosa et al (2008) 20 , demonstrated patients took approximately 8.6 medicaments concomitantly, indicating grave polypharmacy in this part of the population.…”
Section: Resultsmentioning
confidence: 98%
“…Vale salientar que o tratamento da dor pode ser realizado por meio farmacológico (analgésicos não opioides, analgésicos opioides e adjuvantes), não farmacológicos (intervenção psicológica, física ou radioterapia) e invasivos (analgesia intratecal, bloqueio nervoso, cirurgia paliativa, neurocirurgia). Ocorrências da dor são observadas em pacientes em todo o mundo, acometendo até 80% dos pacientes durante os estágios do câncer, sendo que metade dos casos descrevem-na como moderada e 30% como insuportável (27) . Ao observar os principais fármacos presentes no controle de sintomas destes idosos, é perceptível a necessidade de reavaliação para readequação da farmacoterapia, uma vez que a presença da dor e sua intensidade nesses indivíduos são representativas, associando às intervenções da área nutricional, psicológica e fisioterápica, de modo a proporcionar uma melhora na qualidade de vida dessa população.…”
Section: Discussionunclassified